Winning the room - Pease, Jonathan (Ascent Audio, 2023)
Win in every room. Cultivate an authentic connection with your audience, no matter what. Conquer your public speaking fears, learn how to be likable, how to present for work, how to give compelling pitch meetings, and how to be a person who wins through highly effective communication techniques. Winning the Room teaches public speaking skills applicable to everybody, in any situation. Become a great public speaker with guidance from an expert. Do you get nervous before a presentation? Do you find yourself rambling and losing your point? In Winning the Room, award-winning creative and communications director, thought leader, and author Jonathan Pease (JP) uses road-tested techniques to take you on a fun, yet practical journey to becoming a fearless storyteller people buy from-emotionally and financially. In Winning the Room, find: a tight, actionable, and memorable system for how to build trust and be great at different types of public speaking moments; how to turn nervous energy into passion and charisma that people engage with; and how to apply these skills to various settings like keynotes, pitch meetings, presentations, and everyday conversations with friends and family. If you liked Cues, Everyday Business Storytelling, or Your Story Well Told, you'll love Winning the Room.